Characterising the relationship between migration and stigma affecting healthcare engagement among female sex workers in Lomé, Togo. Issue 10 (3rd October 2019) - Lasater, Molly E.; Grosso, Ashley; Ketende, Sosthenes; Lyons, Carrie; Pitche, Vincent Palokinam; Tchalla, Jules; Anato, Simplice; Sodji, Dométo; Nadedjo, Felicity; Baral, Stefan
ABSTRACT: Migration in West Africa is common and complicates the sustained delivery of comprehensive HIV care programmes for those with specific vulnerabilities to HIV, including female sex workers (FSW). This study evaluated whether migration potentiates the burden of stigma affecting FSW in Lomé, Togo. Respondent driven sampling identified 354 FSW who completed HIV testing and a questionnaire. Multivariable logistic regression was used to identify factors associated with stigma among FSW. Among study participants, 76.3% (270/354) were migrants, with 30.2% (107/354) reporting stigma. Migrant FSW were less likely to report stigma (aOR 0.40; 95% CI:0.22–0.73). FSW who had an abortion (aOR 3.40; 95% CI:1.79–6.30) and were tested for a sexually transmitted infection (STI) or HIV (aOR 2.03; 95% CI:1.16–3.55) were more likely to report stigma. Among FSW, 59.8% (211/353) disclosed selling sex to a health worker. Disclosure was more common among FSW who had been tested for an STI or HIV (36.7%; 77/210), or both (55.7%; 117/210), and resulted in an attenuated but significant association between STI or HIV testing and stigma, indicating that disclosure partially mediated the relationship. These results highlight the need to mitigate healthcare-related stigma affecting FSW, while also considering decentralised HIV testing approaches, including HIV self-testing.